2020
DOI: 10.3389/fmed.2020.00313
|View full text |Cite
|
Sign up to set email alerts
|

Association of the Total White Blood Cell, Neutrophils, and Monocytes Count With the Presence, Severity, and Types of Carotid Atherosclerotic Plaque

Abstract: Background: Previous studies have indicated that white blood cells (WBCs) might contribute to the development of atherosclerosis. However, the associations of WBCs and WBC subgroups with carotid atherosclerotic plaque (CAP) have not been compared. Methods: A cross-sectional study including 3,569 healthy Chinese adults was conducted between January 2016 and December 2018 in Zhengzhou, China, to explore the associations of WBC and WBC subtypes with the presence, severity, and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 36 publications
1
12
0
Order By: Relevance
“…In line with their mechanistic function in the pathology of atherosclerosis, high levels of neutrophils in plasma and inside atherosclerotic lesions have been associated with an increased risk for cardiovascular events ( 63 , 94 ). Indeed, a recent analysis of five large randomized clinical trials showed that the neutrophil–lymphocyte ratio is a readily available inflammatory biomarker that predicts cardiovascular outcomes ( 2 ).…”
Section: The Role Of Inflammation In the Pathogenesis Of Atherosclerosismentioning
confidence: 99%
“…In line with their mechanistic function in the pathology of atherosclerosis, high levels of neutrophils in plasma and inside atherosclerotic lesions have been associated with an increased risk for cardiovascular events ( 63 , 94 ). Indeed, a recent analysis of five large randomized clinical trials showed that the neutrophil–lymphocyte ratio is a readily available inflammatory biomarker that predicts cardiovascular outcomes ( 2 ).…”
Section: The Role Of Inflammation In the Pathogenesis Of Atherosclerosismentioning
confidence: 99%
“…Neutrophils could secrete large amounts of inflammatory cytokines to mediate the inflammatory response. 22 Furthermore, various enzymes released by neutrophils, including myeloperoxidase and superoxide radicals, might accelerate the inflammatory response. In contrast, lymphocytes play the most critical role in anti-inflammation and endothelium protection among the immune system.…”
Section: Discussionmentioning
confidence: 99%
“…An increased NLR includes increased neutrophil counts and/or decreased lymphocyte counts, reflecting the imbalanced inflammation status. Neutrophils could secrete large amounts of inflammatory cytokines to mediate the inflammatory response 22 . Furthermore, various enzymes released by neutrophils, including myeloperoxidase and superoxide radicals, might accelerate the inflammatory response.…”
Section: Discussionmentioning
confidence: 99%
“…Peripheral white blood cell (WBC) count is an easy-accessed marker, representing the severity of systematic response to inflammation or stress. Meanwhile, we note many previous studies have reported the associations between peripheral WBC count and incidence of disease, morbidity and mortality, such as atrial fibrillation [ 23 ], stroke [ 24 , 25 , 26 ], myocardium infarction [ 27 , 28 ], respiratory disease [ 29 , 30 , 31 , 32 , 33 ], acute kidney disease [ 34 ], diabetes mellitus [ 35 , 36 , 37 , 38 ], etc. However, few studies explore the relationship of air temperature and peripheral WBC count.…”
Section: Introductionmentioning
confidence: 89%